1986
DOI: 10.1302/0301-620x.68b1.3941145
|View full text |Cite
|
Sign up to set email alerts
|

Compression screw fixation for displaced subcapital fracture of the femur. Success or failure?

Abstract: We report a prospective study of 198 cases of subcapital fracture of the femur treated by closed reduction and fixation with a sliding compression screw-plate. This was done without regard to the patient's age or the Garden stage of the fracture. Early weight-bearing was encouraged. Of the displaced fractures 23% failed in the first year because of non-union or infection. Of the fractures which united 27% had developed avascular necrosis after three years. Despite this we believe that the sliding 78 THE JOURNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 0 publications
3
26
1
3
Order By: Relevance
“…The type of follow-up will influence the results of the study (Skinner andPowles 1986, Frandsen 1986), and as shown here (Table 1). Therefore, we have also presented our results using an actuarial method, which takes in account patients with different periods of follow-up (Table 2).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The type of follow-up will influence the results of the study (Skinner andPowles 1986, Frandsen 1986), and as shown here (Table 1). Therefore, we have also presented our results using an actuarial method, which takes in account patients with different periods of follow-up (Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, we have also presented our results using an actuarial method, which takes in account patients with different periods of follow-up (Table 2). This statistical method was well described by Dobbs (1980) when assessing total hip replacement and by Skinner and Powles (1986) when assessing femoral neck fracture. When comparing the results of treatment of fracture of the femoral neck, several problems arise.…”
Section: Discussionmentioning
confidence: 99%
“…This secures an optimum utilization of the observations and therefore the highest statistical precision. The actuarial method was well described by Dobbs (1980) when he assessed the survivorship of Stanmore hip replacements, and by Skinner & Powles (1986) when they assessed the failure rate after SSP fixation of femoral neck fractures. A direct comparison with the union rates from previous studies is not possible, but the "survivorship table" ( Table 3) shows all the relevant data concerning union and nonunion from our study.…”
Section: Discussionmentioning
confidence: 99%
“…The union rates after fixation with a SSP were in the beginning unsatisfactory (Charnley 1960, Hargadon et al 1963. The early results of the Richards@ lag-screw design were better (Clawson 1964, Rau et al 1982, and the latest published series have shown results among the best in the treatment of femoral neck fractures (Frandsen et al 1984, Norkild & Sonne Holm 1984, Skinner & Powles 1986. In the few existing comparative studies, SSP fixation was found to be superior both to McLaughlin nailplate fixation (Svenningsen et al 1984) and to sliding nail plate fixation (Nordkild et al 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation